PENGGUNAAN FUZZY INFERENCE SYSTEM (FIS) METODE MAMDANI UNTUK MENENTUKAN KINERJA PELAYANAN PDAM - Anggi Puspitasari (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
Clean water is a basic necessity in carrying out activities for the public in urban and rural that have a direct impact on the health and physical well-being, social and economic community. PDAM is one of the business unit belongs to an area that is engaged in the distribution of water to the public is found in every province and district. Performance is an important component of the PDAM in order to find out whether or not a given service to its customers. The criteria service of PDAM there are Scope of the technical services, Customer growth, the Level of resolution of the complaint, and the Quality of the customers waters. These criteria will be entered into the fuzzy system variables by using Mamdani methode, thus determining the performance PDAM can be determined if the PDAM service performance good, good enough and not good. Result by using Mamdani method from 55 service performance PDAM, there are 16 PDAM with not good Service performance, 21 PDAM with good enough service performance, and there are 17 PDAM with good service performance.Keyword: Fuzzy Inference System, Mamdani Methode, PDAM.